2001
DOI: 10.1074/jbc.m102978200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Laminin Binding Domains of the Lutheran Blood Group Glycoprotein

Abstract: Lutheran (Lu) blood group antigens and the basal cell adhesion molecule antigen reside on two glycoproteins that belong to the Ig superfamily (IgSF) and carry five Ig-like extracellular domains. These glycoproteins act as widely expressed adhesion molecules and represent the unique receptors for laminin-10/11 in erythroid cells. Here, we report the mapping of IgSF domains responsible for binding to laminin. In plasmonic resonance surface experiments, only recombinant Lu proteins containing the N-terminal IgSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…El Nemer et al and our work showed that the ability of RBC to bind soluble laminin increases with increased expression of B-CAM/LU [20][21][22]. However, data from Lee and colleagues have suggested that HD SS RBC account for the SS RBC most adherent to immobilized laminin during continuous flow exerting the physiological shear stress of 1 dyne/cm 2 [16].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…El Nemer et al and our work showed that the ability of RBC to bind soluble laminin increases with increased expression of B-CAM/LU [20][21][22]. However, data from Lee and colleagues have suggested that HD SS RBC account for the SS RBC most adherent to immobilized laminin during continuous flow exerting the physiological shear stress of 1 dyne/cm 2 [16].…”
Section: Introductionmentioning
confidence: 79%
“…Both spliceoforms contain five identical extracellular immunoglobulin (Ig) superfamily (SF) domains, and both B-CAM and LU recombinant proteins expressed on the cell surface bind well to soluble and immobilized laminin [20,21]. Our previous studies of SS RBC showed about 50% more B-CAM/LU molecules on lowdensity (LD) SS RBC enriched in reticulocytes than on high-density (HD) SS RBC [21,22] and SS reticulocytes themselves express about four times as much B-CAM/LU than do mature SS RBC [20].…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular domain of Lu contains N-glycosylation consensus motifs. Recently it was reported that Ig-like domains 1-3 are involved in binding to laminin ␣5 (27,29), but the N-glycosylation motifs were not found to be involved in laminin binding. A bacterial Lu recombinant protein that we initially prepared did not bind to laminin-10/11 (data not shown), suggesting that proper glycosylation is required to ensure proper folding.…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic mouse hearts that overexpress laminin ␣5, Lu levels are elevated, suggesting that the increased ␣5 in cardiomyocyte basement membranes recruits additional Lu to the cell surface through a direct interaction. Although the laminin-binding site on Lu has been mapped to a first approximation (20,27,29), there is little insight into the structural basis for Ig superfamily members binding to laminins. To understand better the interaction between Lu and the laminin ␣5 chain, it is important to determine the site of Lu binding on ␣5.…”
mentioning
confidence: 99%
“…2). The Lutheran glycoprotein, a membrane protein belonging to the immunoglobulin superfamily, has been shown to act as a specific receptor for laminin in cell-matrix interaction (17). Furthermore, the 4F2 heavy chain antigen (also known as CD98) was identified in SH-SY5Y, A549, LoVo, and the Sup-B15 leukemia cell lines.…”
Section: Figmentioning
confidence: 99%